2018
DOI: 10.1186/s13033-018-0206-2
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to gender-based violence and depressive symptoms among transgender women in Cambodia: findings from the National Integrated Biological and Behavioral Survey 2016

Abstract: BackgroundTransgender women are at significant risk of HIV, and they face intersecting barriers to health, social, and legal services. However, data regarding the unique needs and experiences of transgender women are globally scant. This study examined the relationship between gender-based violence and depressive symptoms among transgender women in Cambodia.MethodsThis cross-sectional study included 1375 sexually active transgender women recruited by using the respondent-driven sampling method in the capital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Our previous studies showed that transgender women in Cambodia also experience other issues in their daily life. They include gender-based violence, social stigma, and discrimination in different settings, substance abuse, social marginalization, and subsequent mental health problems [8,19,20]. These issues may create significant barriers to receiving regular HIV testing and early treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that transgender women in Cambodia also experience other issues in their daily life. They include gender-based violence, social stigma, and discrimination in different settings, substance abuse, social marginalization, and subsequent mental health problems [8,19,20]. These issues may create significant barriers to receiving regular HIV testing and early treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This means transgender women were about 49 times more likely to be infected with HIV than the general adult population [ 2 ]. In addition, transgender women face many health and non-health issues, including poor sexual and reproductive health, barriers in accessing health services due to stigma and discrimination, mental health problems, limited social support, and limited employment opportunities [ 5 8 ]. To address these concerns, urgent interventions have been suggested for HIV prevention and linkage to care and treatment services for transgender women globally [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transgender women experience multiple, intersecting socio-structural risks that increase their vulnerability to HIV, including stigma and discrimination, gender-based violence, lack of social and legal recognition of their affirmed gender, and exclusion from employment and educational opportunities [3, 4]. These situations may expose them to subsequent mental health problems or vice versa [57]. Among transgender women living with HIV, these systems of oppression can seriously compromise their sustained access to life-saving treatment and care [3, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Enacted, perceived, and anticipated sexual behavior stigmas were common and greater exposure to stigma accounted for the observed inequality in depression between TGW and cisMSM. Associations between stigma and depression among TGW are well-established (9,14,17,36). However, there are few studies that include both cisgender comparison groups as well as stigma measures (39), traditionally precluding tests of the hypothesis that stigma mediates mental health inequalities (40).…”
Section: Discussionmentioning
confidence: 99%
“…Minority stress theory posits that stigma potentiates depression and other negative mental health outcomes among sexual and gender minorities (11)(12)(13). Indeed, associations between stigma and psychological distress or depression have been established among TGW and cisMSM in a number of countries (9,(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%